Efficient analysis of cyclic laterally loaded piles - W.O. McCarron (Results in Engineering, 2021)
The analysis and design of piles subjected to lateral cyclic loads that induce significant plastic responses requires numerical models for the lateral soil resistance capable of representing the fundamental soil responses observed in such conditions. A bounding surface plasticity model with traditional p-y concepts has been implemented in a finite element model and successfully benchmarked against physical tests revealing significant cyclic responses in both one- and two-way loading conditions. The model includes two kinematic hardening surfaces and a fixed limit surface beyond which the kinematic surfaces cannot pass. The benchmarking effort resulted in standardized values for several model parameters for p-y applications. The remaining model parameters are easily calibrated against the expected p-y response under monotonic loading conditions for fine grained soils. The analysis method is extremely efficient, requiring the same level of effort as that typical of traditional p-y techniques. The results presented demonstrate that the model accurately reproduces observed pile cyclic hysteresis, plastic energy dissipation, and stiffness degradation, all of which are neglected in traditional elasticity-based p-y models. It has distinct advantages for static and dynamic analyses involving complex loading histories involving significant plastic soil response and is suitable for site specific analyses. This study is confined to planar conditions, but similar models have been implemented for arbitrary loading directions.